Rapid and Highly Sensitive Method for Influenza A (H1N1) Virus Detection - Su, Li-Chen; Chang, Chung-Ming; Tseng, Ya-Ling; Chang, Ying-Feng; Li, Ying-Chang; Chang, Yu-Sun; Chou, Chien (Analytical chemistry (Washington), 2012)
In this study, we applied the developed paired surface plasma waves biosensor (PSPWB) in a dual-channel biosensor for rapid and sensitive detection of swine-origin influenza A (H1N1) virus (S-OIV). In conjunction with the amplitude ratio of the signal and the reference channel, the stability of the PSPWB system is significantly improved experimentally. The theoretical limit of detection (LOD) of the dual-channel PSPWB for S-OIV is 30 PFU/mL (PFU, plaque-forming unit), which was calculated from the fitting curve of the surface plasmon resonance signal with a S-OIV clinical isolate concentration in phosphate-buffered saline (PBS) over a range of 18–1.8 × 106 PFU/mL. The LOD is 2 orders of magnitude more sensitive than the commercial rapid influenza diagnostic test at worst and an order of magnitude less sensitive than real-time quantitative polymerase chain reaction (PCR) whose LOD for S-OIV in PBS was determined to be 3.5 PFU/mL in this experiment. Furthermore, under in vivo conditions, this experiment demonstrates that the assay successfully measured S-OIV at a concentration of 1.8 × 102 PFU/mL in mimic solution, which contained PBS-diluted normal human nasal mucosa. Most importantly, the assay time took less than 20 min. From the results, the dual-channel PSPWB potentially offers great opportunity in developing an alternative PCR-free diagnostic method for rapid, sensitive, and accurate detection of viral pathogens with epidemiological relevance in clinical samples by using an appropriate pathogen-specific antibody.